Clearing of corneal argyrosis by YAG laser. Issue 12 (December 1989) - Geyer, O; Rothkoff, L; Lazar, M
Abstract : A 75-year-old woman with corneal argyrosis was treated by a Q-switched Nd-YAG laser iridotomy after acute angle closure glaucoma. Each laser shot caused clearance of the argyrotic deposits anterior to the iridotomy site. The same effect was seen when a preventive iridotomy was performed in the other eye. The areas of clear cornea remained unchanged for a follow-up period of eight months.